Exercise-Related Oxidative Stress as Mechanism to Fight Physical Dysfunction in Neuromuscular Disorders - Siciliano, Gabriele; Chico, Lucia; Lo Gerfo, Annalisa; Simoncini, Costanza; Schirinzi, Erika; Ricci, Giulia (Frontiers in Physiology, 2020)
Neuromuscular diseases (NMDs) are a group of often severely disabling disorders characterized by dysfunction in one of the main constituents of the motor unit, the cardinal anatomic-functional structure behind force and movement production. Irrespective from the different pathogenic mechanism specifically underlying these diseased condition genetically determined or acquired, and the related molecular pathways involved in doing that, oxidative stress has often been shown to play a relevant role within the chain of the events that induce or at least modulate the clinical manifestations of these disorders. Due to such a putative relevance of the imbalance of redox status occurring in contractile machinery and/or its neural drive in NMDs, the physical exercise appears as one of the most important conditions able to positively interfere along an ideal axis going from a deranged metabolic cell homeostasis in motor unit components to the reduced motor performance profile exhibited by the patient in everyday life. If so, it comes out that it would important to identify a proper training program, suitable for load and type of exercise, able to improve motor performance in adaptation and response to such an homeostatic imbalance. The review therefore analyzes the role of different exercise trainings on oxidative stress mechanisms, both in healthy and in NMDs, also including preclinical studies, to elucidate at which extent these can be useful to counteract muscle impairment associated to the disease, with the final aim to improve physical functions and quality of life of NMD patients.